Nomophobia: A Modern Challenge to Sports Performance, Athlete Anxiety & Self-esteem - Singh, Maninder (Thapar Institute of Engineering and Technology, 2025)
The purpose of this study was to assess the impact of nomophobia (no mobile phobia) on sports performance. Participants (N=87) were athletes who played sports professionally. Sports anxiety and self-esteem were taken as mediators to gain further insight into the topic. Nomophobia Questionnaire (NMP-Q), Rosenberg self-esteem Scale (RSE), Sports Performance Perceptions Scale (SPPS), and Sports Anxiety Scale-2 (SAS-2) were the tools used to gather the data. Data was collected through Google forms. SPSS 25 was used to analyse the compiled the data. Results revealed that there is a significant negative correlation between nomophobia and sports performance and the impact of nomophobia on sports performance can be explained by a full mediation through sports anxiety and self-esteem.
Keywords: Nomophobia; Sports Anxiety; Self-Esteem; Sports Performance; Sports Psychology